2022
DOI: 10.1088/1748-9326/ac435e
|View full text |Cite
|
Sign up to set email alerts
|

Effects of demand-side restrictions on high-deforestation palm oil in Europe on deforestation and emissions in Indonesia

Abstract: Demand-side restrictions on high-deforestation commodities are expanding as a climate policy, but their impact on reducing tropical deforestation and emissions has yet to be quantified. Here we model the effects of demand-side restrictions on high-deforestation palm oil in Europe on deforestation and emissions in Indonesia. We do so by integrating a model of global trade with a spatially explicit model of land-use change in Indonesia. We estimate a European ban on high-deforestation palm oil from 2000–2015 wou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 47 publications
(33 reference statements)
1
15
0
Order By: Relevance
“…For example, microbial processes are being used to address environmental and societal problems in the palm oil industry. Palm oil is commonly used in household products, but the harvesting of palm oil trees has caused massive deforestation and societal consequences (Busch et al, 2022 ; Kadandale et al, 2019 ).The ongoing development of microbial processes to produce palm oil provides a preferable source of these molecules (Abeln & Chuck, 2021 ; Whiffin et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, microbial processes are being used to address environmental and societal problems in the palm oil industry. Palm oil is commonly used in household products, but the harvesting of palm oil trees has caused massive deforestation and societal consequences (Busch et al, 2022 ; Kadandale et al, 2019 ).The ongoing development of microbial processes to produce palm oil provides a preferable source of these molecules (Abeln & Chuck, 2021 ; Whiffin et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is possible that reduced meat consumption and production can have positive spill-overs in other countries through reduced demand for feed crop production overseas. A lot of processed food uses palm oil, which is entirely produced overseas, typically with large environmental impacts (Busch & Austin, 2022). If processed mat alternatives contain palm oil this could affect the environmental footprint of the UK abroad.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, consumers in the European Union, for example, demand palm oil products from Indonesia and Malaysia that are free from deforestation(Gaveau et al 2018), which burden these countries to ensure deforestation-free export commodities. However, recent research has suggested that banning imports from the European Union of deforestation-free commodities may have a much less signi cant impact on preventing forest loss than was originally expected(Busch et al 2022). Following that, Indonesian palm oil companies began exporting palm oil to China without NDPE commitments.…”
mentioning
confidence: 99%